Determinan Kepercayaan, Lingkungan Sosial, Pendapatan Dan Efikasi Keuangan Terhadap Minat Menabung di Lembaga Keuangan Syariah - Indana Afriyanti; Agus Arwani (Journal of Islamic Economics and Finance, 2022)
This study aimed to determine the effect of trust, social environment, income and financial efficacy on interest in saving in Islamic financial institutions. This research is a type of quantitative research. The data collection method in this study was a questionnaire using a sample of 100 respondents. The sampling technique is probability sampling with a simple random sampling method. This study uses multiple linear regression analysis methods and the data is processed with SPSS version 25 software. The results of this study indicate that partially social environment and efficacy have a significant effect on interest in saving in Islamic financial institutions, while trust and income have no significant effect on interest in saving in institutions. Islamic finance. then simultaneously trust, social environment, income, and financial efficacy affect the interest in saving in Islamic financial institutions. The implications for Islamic financial institutions need to make people feel confident because a person's belief or self-confidence can eliminate doubts about doing something, including in terms of saving. And it is necessary to create a good social environment because the value of a good social environment will encourage people's interest to save in Islamic financial institutions. Whereas. the trust and income variables have no influence on the interest in saving in Islamic financial institutions. This means that Islamic financial institutions need to increase socialization and public education to the public so that they can be more confident and interested in using their products.